NILAI PENDIDIKAN ISLAM DALAM KITAB AQIDATUL AWWAM DAN IMPIKASINYA DI ERA DISTRUPSI - Syukri, Makmur; Sidik, Muhammad; Yogaswara, Dody; Zakiah, Netty (Universitas Al-Amien Prenduan, 2019)
Because of the proliferation of do-it-yourself internet and technology during the disruptive era, Muslims now have to exercise more discerning judgement when deciding what information and digital da'wah to accept online. Muslims have a challenge in this area since they are urged to exercise more discernment in their consumption of the vast amounts of digital information and propaganda available today. Two issues arose as a result of this investigation's findings: 1. Sayyid Ahmad Al-Marzuky, in his book Aqidatul Layman, explains why learning about aqidah is important; 2. Implications for today's society of the values espoused in aqidah education, as stated by Sayyid Ahmad Al-Marzuky in his book Aqidatul Awwam, in light of the prevailing disarray. This kind of research is often done at a library. The Book of Aqidatul Awwam, translated and published by